Iraq : U.S. Regime Change Efforts and Post-War Governance. (U.S. Congressional Research., 2003)
Reviews current issues concerning the U.S.-led war to remove Iraqi President Saddam Hussein and his Ba'ath Party regime. Provides background on past attempts to oust Saddam Hussein, major factions opposed to Saddam Hussein, schisms among factions, and Bush Administration strategy and Operation Iraqi Freedom. Discusses post-war governance issues, including establishing Iraqi self-rule, post-war U.S.-led operations, international role in peacekeeping, and possible prosecution of the deposed regime for war crimes. Outlines Congressional reactions.